Toward an Integrated History and Philosophy of Diagrammatic Practices. Issue 2 (1st June 2020) - Ambrosio, Chiara
Abstract: This article offers an overview of current approaches to the study of diagrams and their roles in scientific knowledge making. The discussion develops in three parts. The first investigates and questions historical and philosophical analyses of the suppression of diagrams in the nineteenth and twentieth centuries. It attempts to sketch an alternative historiography of diagrammatic practices in which the insights of advocates of diagrammatic reasoning in a time of "objectivity without images" take center stage. The second part turns to the American philosopher, scientist, and logician Charles Sanders Peirce as a representative defender of diagrammatic reasoning and diagrammatic representation in the late nineteenth century, and it investigates his legacy on current approaches to diagrams. The final part exposes a puzzling paradox in the literature, characterizing it as a false dichotomy between "the representational view" and the "object-based view" of diagrams. The article concludes that this dichotomy reveals more about the identities of scholars embracing particular disciplinary traditions than about diagrams themselves, and it suggests that this can be overcome by attending to diagramming as a practice at the intersections of representation, manipulation, and experimentation.